Effects of Processing on Chemical Composition of Extracts from Sour Cherry Fruits, a Neglected Functional Food - Francesco Cairone; Caterina Fraschetti; Luigi Menghini; Gokhan Zengin; Antonello Filippi; Maria Antonietta Casadei; Stefania Cesa (MDPI AG, 2023)
Sour cherries fruits (Prunus cerasus L., syn P. cerasus var. austera) are locally known as "visciola di Sezze", due to the name of the city where they are traditionally cultivated in Lazio Region, Italy. Fruit samples from three harvesting years (June 2019, 2020 and 2021), were submitted to a protocol of analyses to detect the bioactive content based on year of harvest, freezing, homogenization and thermic treatments. Polyphenolic components, particularly anthocyanin compounds, were extracted, purified and analyzed by HPLC-DAD and DI-ESI-MS. An anthocyanin content between 0.24 and 21 mg/g fresh weight and a flavonols content between 0.04 and 0.2 mg/g fresh weight were found, depending on the harvest year and the applied procedures. Anthocyanins, besides being the principal components, were mainly represented by cyanidin-3-glucosyl-rutinoside (about 80%), a not particularly widespread molecule, mostly accounting for polyphenolic content. Color analysis and anti-radical activity of the different obtained extracts were performed with the aim to correlate organoleptic characters and health potential to the detected anthocyanins and flavanols content. Results show that immediate post-harvest freezing is the best way to preserve the bioactive content, the correlated color expression and anti-radical activity.